Differential Nr4a1 and Nr4a3 expression discriminates tonic from activated TCR signalling events in vivo - Jennings,E; Elliot,TAE; Thawait,N; Kanabar,S; Yam-Puc,JC; Ono,M; Toellner,K-M; Wraith,DC; Anderson,G; Bending,D (2019)
Summary Nr4a receptors are activated by T cell receptor (TCR) and B cell receptor (BCR) signalling and play key roles in T cell differentiation and promoting T cell exhaustion. How TCR signalling pathways regulate Nr4a receptors and their sensitivities to different physiological types of TCR signalling (e.g. tonic versus activating) remains unknown. Here we utilise Nr4a1/Nur77-GFP and Nr4a3 -Tocky mice to elucidate the signalling pathways that govern Nr4a receptor expression in CD4 + and CD8 + T cells. Our findings reveal that Nr4a1-3 are Src family kinase-dependent. Moreover, Nr4a2 and Nr4a3 are abolished by calcineurin inhibitors and bind NFAT1, highlighting a necessary and sufficient role for NFAT in the control of Nr4a2 and Nr4a3 , but redundancy for NFAT for Nr4a1 . During T cell development, Nr4a1 is activated by tonic signalling during TCR-beta selection in the thymus, whilst Nr4a3 requires cognate peptide:MHC interactions for expression. Thus, due to differential sensitivity of Nr4a1 and Nr4a3 to TCR signalling pathways, T cells undergoing tonic versus activating TCR signalling events can be distinguished in vivo.